PENGARUH TOBAT TERHADAP AKHLAK PERSPEKTIF AL-GHAZALI (450-505 H/1058-1111 M) - Neli Agustin (ISTIQAMAH: Jurnal Ilmu Tasawuf, 2023)
This study discusses the effect of repentance on akhlak in al-Ghazali's perspective. Humans are created with good and bad qualities in themselves. However, God only commands humans to always do good and forbid doing bad. Sufism comes as one solution in this regard. In Sufism there is a penitential station as the initial ladder to get close to God. The repentance seems to have a relationship with human actions, also called akhlak. Al-Ghazali is a Sufism figure who discusses this. Therefore, the writer examines the concept of repentance al-Ghazali and looks for how the effect of repentance in his framework. This study uses a qualitative method with Sufism approach and is included in the type of library research because the main object is books by al-Ghazali. Based on the research that the author has done, it is found that the concept of repentance al-Ghazali is returning from immorality to obedience and includes three things namely, science, circumstances, and charity. For him repentance is required to constantly remember humans are not free from sin, both small and large sins. Besides that, knowing the sins from which you must repent is also obligatory. Thus, someone will be able to repent perfectly accompanied by the conditions. Based on the concept of repentance al-Ghazali, according to the author has an influence on akhlak. If someone already knows his actions including bad deeds and sin, then he repents from it seriously and continuously, then he can become a habit. Then it can form traits that are embedded in the soul, giving rise to various good deeds done later easily and easily, without the need for thought and consideration. Thus it is called akhlak.